Bahasa Inggris - Jerina Fujiantie; Endro S Efendi; Sy. Nurul Syobah; Firdaus Muhammad (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
For journalists, the development of the digital age is like two blades for their profession. Digitization makes it easy for journalists to find news topics over the Internet. A wealth of information and news, whether from the general public or from journalists, contributes to the potential for false information, or so-called hoaxes. Also, the cultural issues of covering journalists have turned into journalist transfers. This condition occurs because many journalists are out of balance with their understanding of the ethical code of journalism. Journalists, especially Muslim journalists, are tasked with performing the prophetic mission of telling the truth and the good news and issuing warnings. One of the efforts to implement the concept of prophetic journalism for journalists is the Journalist Skills Test organized by the Press Council. This article describes the value of prophetic journalism in the journalism proficiency testing process. As a result of the research obtained, the Journalism Proficiency Test, which includes an ethical code as test material, consciously or unknowingly seeks to implement prophetic values in the journalism profession. The 11 Journalism Proficiency Test Criteria implement the characteristics of the Prophet (Shiddiq, Tabligh, Amanah, and Fathonah), the core competencies of prophetic journalism.